Shape recognition using a novel fractal technique - Neil, Geoff; Curtis, K. Mervin; Craven, Michael (Institute of Electrical and Electronics Engineers, 1996)
Fractal transformations are an exciting new scale invariant shape recognition technique developed by the authors. They have been successfully used for spatially invariant shape recognition using a cumbersome rotational invariance algorithm. Within this paper a new rotational invariance algorithm is presented which makes the recognition process inherently rotationally invariant. A full discussion of fractal recognition is given and previous results discussed. The new algorithm is detailed and applied to a difficult recognition problem. The results of this application show that the new algorithm is successful in achieving the desired effect.
ORCID Source: Michael P. Craven